Compton scattering in TFD formalism - D. S. Cabral; A. F. Santos (European Physical Journal C: Particles and Fields, 2023)
Abstract In this paper, the cross section for the Compton scattering process at finite temperature is calculated. Temperature effects are introduced using the Thermofield Dynamics (TFD) formalism. It is a real-time finite temperature quantum field theory. Our result shows that thermal effects become relevant as the temperature increases. A comparison between the TFD and closed-time path results is presented.